2013
DOI: 10.1038/ni.2648
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs of the miR-17∼92 family are critical regulators of TFH differentiation

Abstract: T follicular helper (T FH ) cells provide critical help to B cells during humoral immune responses.Here we report that mice with T cell-specific deletion of miR-17~92 family miRNAs (tKO mice) exhibited severely compromised T FH differentiation, germinal center formation, antibody responses, and failed to control chronic virus infection. Conversely, T cell-specific miR-17~92 transgenic mice spontaneously accumulated T FH cells and developed fatal immunopathology. Mechanistically, miR-17~92 family miRNAs control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
186
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 163 publications
(196 citation statements)
references
References 39 publications
8
186
2
Order By: Relevance
“…Mice with Tcellspecific loss of miR1792 cluster exhibit severely compromised Tfh cell differentiation, germinal center formation, and antibody responses. On the contrary, Tcellspecific miR1792 cluster transgenic mice spontaneously accumulate Tfh cells [99] . miR10a attenuates phenotypic conversion of iTreg cells to Tfh cells by simultaneously targeting Bcl6, a transcription factor critical for Tfh cell differentiation [101] , along with the corepressor Ncor2 [90] .…”
Section: Mirnas and Follicular Helper T Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mice with Tcellspecific loss of miR1792 cluster exhibit severely compromised Tfh cell differentiation, germinal center formation, and antibody responses. On the contrary, Tcellspecific miR1792 cluster transgenic mice spontaneously accumulate Tfh cells [99] . miR10a attenuates phenotypic conversion of iTreg cells to Tfh cells by simultaneously targeting Bcl6, a transcription factor critical for Tfh cell differentiation [101] , along with the corepressor Ncor2 [90] .…”
Section: Mirnas and Follicular Helper T Cellsmentioning
confidence: 99%
“…Several studies have demonstrated that miRNAs are crucial for Tfh cell differentiation and function [99,100] . Mice with Tcellspecific loss of miR1792 cluster exhibit severely compromised Tfh cell differentiation, germinal center formation, and antibody responses.…”
Section: Mirnas and Follicular Helper T Cellsmentioning
confidence: 99%
“…These include lymphoid enhancer‐binding factor 1 (LEF‐1) and T‐cell‐specific transcription factor 1 (TCF‐1), which act upstream of Bcl6 to promote Tfh cell differentiation140, 141, 142; basic leucine zipper transcription factor ATF‐like (Batf), which positively regulates Bcl6 and is important for IL‐4 expression143; interferon regulatory factor 4 (IRF4), which drives differentiation of IL‐12‐stimulated CD4 T cells to Tfh rather than Th1 cells144; achaete‐scute homolog 2 (Ascl2), which induces CXCR5 expression145; c‐Maf, which enhances expression of CXCR5, IL‐21, and IL‐4146; signal transducer and activator of transcription (STAT)s, STAT3 and 4 being particularly important for human Tfh cell differentiation and regulation of IL‐21 expression by human CD4 + T cells121, 147; and forkhead box protein O1 (FOXO1), which can both promote and inhibit Tfh cell differentiation 148. In addition, Tfh cell differentiation is regulated by microRNAs including members of the miRNA‐17‐92 family 149, 150. Bcl6 is a transcriptional repressor and orchestrates the expression of genes involved in Tfh cell migration, differentiation, and function as well as repressing genes involved in alternative fate differentiation 151.…”
Section: T Follicular Helper Cells and Their Role In Bnab Inductionmentioning
confidence: 99%
“…microRNAs regulate gene expression at the posttranscriptional level through mRNA stability and translation (Selbach et al, 2008). microRNAs control multiple aspects of T cell differentiation and activation, from initial signaling events (Li et al, 2007) to the acquisition of effector functions and cytokine production (Muljo et al, 2005;Steiner et al, 2011), the resolution of T cell responses (Zhang and Bevan, 2010;Yang et al, 2012) and the choice of T cell fates including T helper cell lineage (Muljo et al, 2005;Steiner et al, 2011;Baumjohann et al, 2013;Kang et al, 2013;Khan et al, 2013), the formation of memory cells (Khan et al, 2013), and regulatory T cell differentiation (Cobb et al, 2006;Liston et al, 2008;Zhou et al, 2008;Lu et al, 2010).…”
Section: Dicer-deficient Cd4 T Cells Show Heightened Sensitivity To Tmentioning
confidence: 99%